Some English and Ilocano clause structures a contrastive analysis - Lucas, Florendo de la Cruz 1926- (s.n.], 1970)
The study presents a contrastive analysis of English and Ilocano clause structures based on the assumption that the first language habits of the learner interfere with the learning of the second language. It attempts to point out the similarities and differences which tend to determine the ease and difficulty in learning English. The procedure employed was that suggested by Lado in his book "Linguistics Across Cultures". Findings of the study reveal that learning a second language is difficult when a learner is confronted with a great difference in the structural patterns of the two languages. Learning a second language is easy when there is a great degree of correspondence in the structural systems of the two languages.